Warming enhances the effects of nitrogen addition on fungal but not on bacterial diversity in an alpine meadow - Ling Han; Hasbagan Ganjurjav; Guozheng Hu; Jianshuang Wu; Xuexia Wang; Yulong Yan; Yilun Hu; Guoxu Ji; Luobu Danjiu; Qingzhu Gao (Basic and Applied Ecology)
Warming and nitrogen (N) deposition significantly affect soil microbial community characteristics. However, the responses of bacterial and fungal diversity to warming and N deposition, as well as the dominant influencing factors, remain unclear, especially in N-limited and low-temperature ecosystems. We employed a field-controlled experimental design with warming (W, using open-top chambers at +2 °C), N addition (N, 40 kg N ha−1 yr−1 NH4NO3), and their interaction (NW) to simulate their effects on soil microbial community composition and diversity, as well as plant community characteristics. Our results showed a significant decrease in bacterial richness (Chao1) under warming. N addition had a positive effect on bacterial richness (Chao1) but a negative effect on fungal diversity (Shannon and Chao1), which led to a considerable shift in bacterial community composition. Conversely, N addition combined with warming significantly increased fungal diversity but decreased bacterial diversity compared with N addition alone. Bacterial diversity was positively influenced by soil moisture but negatively affected by soil temperature and forb dominance. Fungal diversity was negatively influenced by soil NH4+-N content and belowground biomass. Additionally, our results showed a synergistic effect on fungi owing to changes in plant community composition, while an antagonistic effect on bacterial diversity was observed owing to reduced water and nutrient availability under warming plus N addition. Our findings underscore the importance of considering plant productivity and diversity when examining microbial diversity responses to warming and N addition in alpine meadows.